Evaluation of quality of banana soils through microbial activity in the south the lake of Maracaibo, Zulia state, Venezuela - González García, Hebandreyna; González Pedraza, Ana F.; Atencio, Jhoen; Soto, Anibal (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
The microbial activity can serve as an indicator of the general state of the soil, since it is the reflection of optimal physical and chemical conditions for the development of the metabolic processes of microorganisms that act on the soil, which is why it constitutes an indicator of the dynamics and resource health. With the objective to evaluate the soil quality through microbial activity in banana plantations at the south of Lake Maracaibo, a study was carried out in different production units located in the municipality of Colón of the Zulia state. Lots of banana plants of high and low vigor (AV and BV), for this purpose composite samples the soil at 0-20 cm depth were taken. It was determined: microbial carbon, soil basal respiration, and microbial and metabolic quotient. The results showed that vigor parameters: number of hands per bunch; pseudostem circumference and height of the succession child were significantly higher in VA than in BV, while for microbial carbon, basal soil respiration, and microbial and metabolic ratios, no statistically significant differences were found between vigor lots. The high microbial activity was closely related to the soil texture and, in turn, this positively influenced the biometric parameters of the plants.